Activation of the EGFR/PI3K/AKT pathway limits the efficacy of trametinib treatment in head and neck cancer - Novoplansky, Ofra; Shnerb, Avital B.; Marripati, Divyasree; Jagadeeshan, Sankar; Abu Shareb, Raghda; Conde-Lopez, Cristina; Zorea, Jonathan; Prasad, Manu; Ben Lulu, Talal; Yegodayev, Ksenia M.; Benafsha, Chen; Li, Yushi; et al. (Molecular oncology, 2023)
Blocking the mitogen-activated protein kinase (MAPK) pathway with the MEK1/2 inhibitor trametinib has produced promising results in patients with head and neck squamous cell carcinoma (HNSCC). In the current study, we showed that trametinib treatment leads to overexpression and activation of the epidermal growth factor receptor (EGFR) in HNSCC cell lines and patient-derived xenografts. Knockdown of EGFR improved trametinib treatment efficacy both in vitro and in vivo. Mechanistically, we demonstrated that trametinib-induced EGFR overexpression hyperactivates the phosphatidylinositol 3-kinase (PI3K)/AKT pathway. In vitro, blocking the PI3K pathway with GDC-0941 (pictilisib), or BYL719 (alpelisib), prevented AKT pathway hyperactivation and enhanced the efficacy of trametinib in a synergistic manner. In vivo, a combination of trametinib and BYL719 showed superior antitumor efficacy vs. the single agents, leading to tumor growth arrest. We confirmed our findings in a syngeneic murine head and neck cancer cell line in vitro and in vivo. Taken together, our findings show that trametinib treatment induces hyperactivation of EGFR/PI3K/AKT; thus, blocking of the EGFR/PI3K pathway is required to improve trametinib efficacy in HNSCC.
Gesehen am 14.11.2023